The review of economics and statistics (Amsterdam Elsevier, 1995)
The Review of Economics and Statistics is a general journal of applied (especially quantitative) economics. The Review has published some of the most important articles in empirical economics. From time to time, The Review also publishes collections of papers or symposia devoted to a single topic of methodological or empirical interest.
The Review of economics and statistics ​is published four times a year in February, May, August, and November for the Dept. of Economics, Harvard University by Elsevier Science publishers. Full text articles are available from JSTOR: https://www.jstor.org/journal/revieconstat
Keywords: Economics; ECONOMICS; ECONOMIC STATISTICS; PERIODICALS